CORRECTIVE LOGOPEDIC WORK SYSTEM FOR ELIMINATING SPEECH DEFECTS IN PRESCHOOL CHILDREN - Rakhimova Munirakhan Ilhomovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides recommendations on the corrective speech therapy system for eliminating speech defects in preschool children. The goals and tasks of teaching in groups of children whose speech is not fully developed are explained.